Ambition : the road to perdition - Han, Cheryl Suling (2010)
Shakespeare’s Macbeth is a combination of tragic heroism, fate and ambition, culminating in the death of its titular hero. The play sees Banquo and Duncan posited as sacrificial lambs whose lives must be forgone to make way for Macbeth’s ascension as king, a position from which he will inevitably fall. Macbeth, like the other characters, is a victim of predestination but unlike them, his death is brought about as a consequence of rejecting fortune as beneath him and perceiving himself to have free agency when it does not appear to be the case. The ambition that he is renowned for is not a mere desire for achievement but that which follows Machiavelli’s notion of virtue. His dismissal of the fate that both commands and orders the Macbeth universe exemplifies the famed Machiavellian principle that he follows. It dictates a partial subservience to fortune so as to control her, and at the same time rely on one’s own free will to commit acts of domination in order to attain sovereignty over others. These acts of domination that Macbeth commits under the urging of Lady Macbeth and the uncannily accurate prophecies of the Weird Sisters, go against the order of nature, which are continually referred to through multiple images of natural procreation. In so doing he halts the progression of nature that fate governs but is ultimately punished through poetic justice, first through his conscience, followed by death. The idea of conscience present in such a Machiavellian tragedy where Macbeth fails to control fate puts forth a moral quality to the tragedy. Rooted in the Bradleyian notion of tragic heroism, the morality manifested in the conscience that Macbeth feels after each murder complicates the Machiavellian tragedy in so far as it prevents Macbeth from being thoroughly immoral.